The corelation Length of Time Undergoing Hemodialysis and the Quality of Life of Patients with Chronic Kidney Failure in Cut Nyak Dien Room, RSUD Dr Saiful Anwar Malang - Fitri Istiariningsih; Andi Surya Kurniawan; Kurnia Laksana (PROFESSIONAL HEALTH JOURNAL, 2023)
Patients undergoing hemodialysis therapy experience a decrease in quality of life. This is due to changes in their lives such as limited mobility, a reduced role in society, and decreased productivity. These changes affect the patient's psychological condition, which has an impact on the patient's perception of his life, including quality of life. The aim is to determine the relationship between the duration of hemodialysis and the quality of life in Chronic Kidney Disease (CKD) patients in the Cut Nyak Dien Room at Dr. Saiful Anwar Hospital, Malang. This research design is a non-experimental correlational research design using a cross-sectional approach, involving 74 respondents from chronic kidney disease patients undergoing hemodialysis. This research uses primary data using the KDQOL SF-36. The results of the chi square test showed that there was a relationship between the length of time undergoing hemodialysis and the quality of life of Chronic Kidney Disease patients in the Cut Nyak Dien Room at Dr. Saiful Anwar Hospital, Malang (p value <0.05). It is hoped that the hospital can maintain and improve the quality of service to chronic kidney failure patients by providing appropriate health education so that they understand the changes that will occur in their health.